2015
DOI: 10.1177/1933719114565036
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Normal and Abnormal Early Human Pregnancies

Abstract: Autophagy is an inducible catabolic process by which cells degrade and recycle materials to survive stress, starvation, and hypoxia. The aim of this study was to evaluate autophagy at the fetal-maternal interface, to assess autophagy involvement during the early phase of human gestation, and to explore autophagic modification in case of early abnormal pregnancy outcome. Specimens were collected from first-trimester normal gestations undergoing legal termination of pregnancy and first-trimester sporadic spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…However, in both case, data were obtained from third trimester placenta while we focused on early development when a correct feto-maternal interaction is necessary for normal pregnancy proceeding. To our knowledge, there is only one study that reported an increased autophagy during early pregnancy in villous sample collected from spontaneous miscarriage [ 19 ]. However is not determined if autophagy has been induced as consequence of fetal demise, whereas in our study all analysed samples were collected from alive foetuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both case, data were obtained from third trimester placenta while we focused on early development when a correct feto-maternal interaction is necessary for normal pregnancy proceeding. To our knowledge, there is only one study that reported an increased autophagy during early pregnancy in villous sample collected from spontaneous miscarriage [ 19 ]. However is not determined if autophagy has been induced as consequence of fetal demise, whereas in our study all analysed samples were collected from alive foetuses.…”
Section: Discussionmentioning
confidence: 99%
“…starvation, hypoxia) affecting both normal and complicated pregnancies. In human placentae, expression of autophagic marker has been detected throughout the normal gestation, from the early stage until delivery [ 17 19 ]. High autophagic activity was also reported in placentae (collected at delivery) from pregnancies complicated by IUGR [ 20 22 ] and pre-eclampsia [ 23 25 ], suggesting an important role for autophagy in normal and abnormal placentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by Avagliano et al [91] demonstrated that enhanced expression of LC3-II in villous trophoblasts in spontaneous abortion with increased HIF-1α and cleaved caspase 3 in decidual tissue. Given the fact that the trophoblasts in human placenta have to adapt to the change in microenvironment at the maternal fetal interphase over nine months, gestational age-dependent change in placenta should not be underestimated.…”
Section: Part IImentioning
confidence: 99%
“…Immunofluorescence was performed as previously reported (Avagliano et al, , ; Pryor et al, ). Briefly, paraffin‐embedded 5‐µm tissue sections were deparaffinized in xylene and rehydrated through a graded series of alcohols.…”
Section: Methodsmentioning
confidence: 99%